Impact of Minimal Incision Repair of Rectus Abdominis Diastasis on Quality of Life and Stress Incontinence: A Prospective Study - Asmatullah Katawazai; Göran Wallin; Anna Ärlebäck; Gabriel Sandblom; Gabriel Sandblom (Journal of Abdominal Wall Surgery, 2025)
AimThis study evaluates the impact of the minimal incision repair of rectus abdominis diastasis (MIRRAD) procedure on physical activity, muscle strength, quality of life, and overall satisfaction in women with postpartum rectus abdominis diastasis (PP-RAD).MethodsA cohort of 31 female patients, aged 20–50 years, diagnosed with PP-RAD unresponsive to conservative treatment, underwent the MIRRAD procedure. Assessments were conducted preoperatively and 1 year postoperatively, these included the Modified Abdominal Trunk Function Protocol (MATFP), Disability Rating Index (DRI), and Urinary Disability Index (UDI) questionnaires. Physical activity intensity was monitored using accelerometers.ResultsSignificant improvements were observed in vigorous physical activities (Z = −2.352, p = 0.019), vector magnitude counts per minute (Z = −2.163, p = 0.031), and steps per minute (Z = −3.131, p = 0.002). DRI showed significant improvements in physical tasks like dressing, walking, and strenuous work (Z ranging from −2.705 to −4.603, p < 0.001). UDI indicated significant improvements in urinary symptoms, including reduced frequency (Z = −2.984, p = 0.003) and less urinary leakage (Z = −2.357, p = 0.018). MATFP demonstrated gains in back and abdominal muscle strength (Z = −4.321, p < 0.001) and trunk stability (Z = −3.991, p < 0.001).ConclusionThe MIRRAD procedure significantly improves physical strength, trunk stability, and urinary function, enhancing daily activities and overall physical health in women with PP-RAD. Further research is recommended to evaluate long-term outcomes.